Is the Digital Divide for Orthopaedic Trauma Patients a Myth? Prospective Cohort Study on Use of a Custom Internet Site. Issue 7 (July 2016) - Matuszewski, Paul E.; Costales, Timothy; Zerhusen, Timothy; Coale, Max; Mehta, Samir; Pollak, Andrew N.; O'Toole, Robert V.
Abstract : Objectives: Some have proposed that a so-called digital divide exists for orthopaedic trauma patients and that the clinical usefulness of the Internet for these patients is limited. No studies to date have confirmed this or whether patients would use a provided web resource. The hypotheses of this study were (1) a larger than expected percentage of trauma patients have access to the Internet and (2) if given access to a custom site, patients will use it. Design: Prospective cohort. Setting: Level 1 regional trauma center. Patients: Patients who were 18 years or older with acute operative fractures participated in this study. Enrollment was initiated either before discharge or at initial outpatient follow-up. Intervention: We conducted a survey of demographics, Internet usage, device type, eHealth Literacy, and intent to use the web site. Participants received a keychain containing the web address and a unique access code to our custom orthopaedic trauma web site. Main Outcome Measurements: Percentage of patients with Internet access and percentage of patients who visited the web site. Results: One hundred twelve patients were enrolled. Ninety-three percent (104/112) reported having Internet access ( P < 0.0001). Only increasing age predicted lack of access ( P < 0.015; odds ratio, 0.95). Most (95%, 106/112) planned to visit our site; however, only 11% ( P < 0.001) accessed it. Conclusions: The digital divide is a myth in orthopaedic trauma. Despite widespread access and enthusiasm for our web site, few patients visited. This cautions against the allocation of resources for patient-specific web sites for orthopaedic trauma until a rationale for use can be better delineated. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content Is Available in the Text.